Relationship Between Dietary Fiber Intake and Short‐Chain Fatty Acid–Producing Bacteria During Critical Illness: A Prospective Cohort Study. Issue 3 (6th August 2019) - Fu, Yichun; Moscoso, Dagmara I.; Porter, Joyce; Krishnareddy, Suneeta; Abrams, Julian A.; Seres, David; Chong, David H.; Freedberg, Daniel E.
Abstract: Background: Dietary fiber increases short‐chain fatty acid (SCFA)‐producing bacteria yet is often withheld in the intensive care unit (ICU). This study evaluated the safety and effect of fiber in ICU patients with gut microbiome sampling. Methods: This was a retrospective study nested within a prospective cohort. Adults were included if newly admitted to the ICU and could receive oral nutrition, enteral feedings, or no nutrition. Rectal swabs were performed at admission and 72 hours later. The primary exposure was fiber intake over 72 hours, classified in tertiles and adjusted for energy intake. The primary outcome was the relative abundance (RA) of SCFA producers via 16S RNA sequencing and the tolerability of fiber. Results: In 129 patients, median fiber intake was 13.4 g (interquartile range 0–35.4 g) over 72 hours. The high‐fiber group had less abdominal distension (11% high fiber vs 28% no fiber, P < .01) and no increase in diarrhea (15% high fiber vs 13% no fiber, P = .94) or other adverse events. The median RA of SCFA producers after 72 hours was 0.40%, 0.50%, and 1.8% for the no‐, low‐, and high‐fiber groups ( P = .05 for trend). After correcting for energy intake, the median RA of SCFA producers was 0.41%, 0.32%, and 2.35% in the no‐, low‐, and high‐corrected‐fiber categories ( P < .01). These associations remained significant after adjusting for clinical factors including antibiotics. Conclusions: During the 72 hours after ICU admission, fiber was well tolerated, and higher fiber intake was associated with more SCFA‐producers.